Legal Enforcement of Corruption Criminal Act PT Asuransi Jiwasraya (Case Study of Decision 2931 K/Pid. Sus/2021) - S, Adelina Mariani; Sitanggang, Djernih; Sudjiarto, Tatok (Journal of Social Work and Science Education, 2024)
This study aims to evaluate the judicial decision in the corruption case involving PT Asuransi Jiwasraya (Persero) based on Verdict Number 2935 K/Pid.Sus/2021, as well as examine the liability of insurance companies in cases of policy payment failures. The research employs a normative legal method with a statute approach, relying on secondary data from documents and legal literature. Data analysis is conducted qualitatively by categorizing and selecting data, which is then analyzed deductively and presented descriptively. The findings indicate that the judge in Verdict Number 2935 K/Pid.Sus/2021 affirmed the legal violations that harmed the policyholders. The liability of the insurance company can be addressed preventively through regulations that provide legal certainty and repressively through criminal law enforcement and civil lawsuits by policyholders for PT Asuransi Jiwasraya (Persero)’s default. Law enforcement authorities are expected to be more proactive and stringent in handling corruption cases, and the government needs to enhance regulations related to policyholder protection, including the establishment of a Policy Guarantee Institution Act. Educating the public about their rights as insurance policyholders is also crucial for raising awareness and vigilance. Further research is necessary to explore the factors contributing to insurance companies’ failures to fulfill their obligations and the effectiveness of existing regulations. Implementing these recommendations is anticipated to create a more just and transparent legal environment, providing better protection for the public.